The Effectiveness of Using Eco-Friendly Bag to Support Sustainable Development Goals: A Review - Annisa Indah Pratiwi; Nadia Rizki Ariyani; Chintya Komala Sari; Abdul Rahman (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2024)
Nowadays, most people use eco-friendly bags as alternatives to plastic grocery bags. This comes from the government's strategy of prohibiting plastic bag use and requiring the use of eco-friendly supermarket bags instead. Eco-friendly bags are the most recent developments in supermarket bags made from environmentally friendly raw materials. However, using eco-friendly bags is not the ideal option because it generates new trash clusters as a result of their use and contributes to the impact of climate change. This article examines the effectiveness of using eco-friendly bags in reducing plastic waste and how it relates to SDG 13. This research uses qualitative methods related to analysing the environmental impact of environmentally friendly bags. It was found that bio-based plastics had the lowest GWP values. Several solutions to the problem of plastic bag pollution have been offered, including the development of new biodegradable bag technology, making policies or other incentives encouraging people to reuse shopping bags, and researching eco-friendly bag innovation in Indonesia using LCA.